2019
DOI: 10.3389/fgene.2018.00720
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Host and Viral Genome and Their Influence on HIV Disease

Abstract: The course of Human Immunodeficiency Virus type 1 (HIV) infection is a dynamic interplay in which both host and viral genetic variation, among other factors, influence disease susceptibility and rate of progression. HIV set-point viral load (spVL), a key indicator of HIV disease progression, has an estimated 30% of variance attributable to common heritable effects and roughly 70% attributable to environmental factors and/or additional non-genetic factors. Genome-wide genotyping and sequencing studies have allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 69 publications
(96 reference statements)
0
29
0
1
Order By: Relevance
“…The interaction of viruses and host factors has been well documented in the literature [10,[40][41][42][43][44]. Recently, we have started to expand upon our understanding of host-virus interactions to include non-coding RNAs [21,[45][46][47].…”
Section: Host-transcribed Non-coding Rnas Regulating Hiv-1 Entry Repmentioning
confidence: 99%
“…The interaction of viruses and host factors has been well documented in the literature [10,[40][41][42][43][44]. Recently, we have started to expand upon our understanding of host-virus interactions to include non-coding RNAs [21,[45][46][47].…”
Section: Host-transcribed Non-coding Rnas Regulating Hiv-1 Entry Repmentioning
confidence: 99%
“…The high mutation rate of the HIV genome is one of the reasons for the formation of multiple HIV variants, which have new antigen properties that allow the virus to escape from an immune response (Rogozin et al, 2005;Cuevas et al, 2015). However, polymorphisms in the human genome can also influence the susceptibility to and severity of HIV infections (Le Clerc et al, 2019;Tough and McLaren, 2019). The candidate gene studies revealed a 32-bp deletion in the CCR5 gene (CCR5-32) encoding a co-receptor that is essential for 12 http://www.rna-society.org/virbase/index.html 13 http://210.46.85.180:8080/vmireg 14 http://crdd.osdd.net/servers/virmirna HIV binding to CD4+ cells.…”
Section: Genomics Datamentioning
confidence: 99%
“…1,2 Several HLA genes or haplotypes appear to influence disease progression, although the effects are complex and may depend on interactions with other host and viral genes. 3 Before the discovery of the role of C-C chemokine receptor (CCR) gene polymorphism in HIV infection and disease progression, only genes of the HLA system were thought to influence HIV disease progression. In the 1990s, studies confirmed the protective role of homozygosity for a 32-bp deletion in CCR5 open reading frame (ORF, CCR5 D32) against HIV infection.…”
mentioning
confidence: 99%
“…In the 1990s, studies confirmed the protective role of homozygosity for a 32-bp deletion in CCR5 open reading frame (ORF, CCR5 D32) against HIV infection. [1][2][3] The CCR5 D32 allele is predominantly found in European populations, with no or rare occurrences in Asians and native populations from Africa, the Americas, and Oceania. 4 The presence of one copy of the deleted CCR5 gene also influences the course of disease, as the onset of AIDS occurs later for some heterozygous persons than for those homozygous for the wild-type (wt) CCR5 gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation